PENGUATAN MOTIVASI MENULIS CERPEN MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM PENINGKATAN LITERASI SASTRA - Haryanto, Yusuf; Nurjam’an, Muhammad Ichsan; Nina, Nina; Apriani, Salamah; Bujaya, Muhammad (Jurnal Metamorfosa, 2025)
A B S T R A C T This study aims to determine the effect of the Problem-Based Learning (PBL) model on fantasy story writing skills, as measured by the writing motivation of seventh-grade students at SMP Negeri 2 Cibungbulang, Bogor. This study employed a quantitative research method with an experimental approach. To determine the effect of the Problem-Based Learning (PBL) model, the sample was divided into two classes: high- and low-motivation. Data collection began with a questionnaire to determine motivation levels, followed by instructional sessions. The results of the lecture and PBL tests were then compared to determine the influence of interest and the model used. A two-way ANOVA calculation revealed that the average score for class A1B1 was 82.95, for class A1B2 71.3, for class A2B1 73.6, and for class A2B2 49.4. In addition, Fcount > Ftable with: (1) Factor A (Motivation): Fcount = 29.3709 > Ftable = 3.96676; (2) Factor B: Fcount = 38.6541 Ftable = 3.96676; (3) Factor C (Interaction between Motivation and Model): Fcount 4.73701 > Ftable = 3.96676. Thus, the results of the comparison of Fcount > Ftable show that there is an influence of the Problem Based Learning (PBL) model on the skills of writing fantasy story texts in terms of the writing motivation of class VII students of SMP Negeri 2 Cibungbulang Bogor.